Utilization of Artificial Intelligence (AI) in Information Systems to Improve Business Efficiency - Muhammad Nasrullah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Artificial Intelligence (AI) in information systems is a tool that can be used to improve business efficiency. This research aims to review the utilization of AI in information systems, especially in the context of Accounting, Management Information Systems, and Human Capital Management Information Systems, it is very important to understand the potential and examples of applications that apply AI in information systems in a business context.The research uses a literature research methodology which synthesizes this literature review by grouping similar extracted data according to the results measured to answer the objectives. It was concluded that the utilization of artificial intelligence (AI) in Business Accounting Information Systems, Business Management Information Systems, and Business Human Capital Management Information Systems has great potential to improve business efficiency. AI can automate routine tasks, improve data analysis, and provide deeper insights in these three aspects of management. In addition, AI can also help in risk management, financial analysis, and better decision-making.